2018
DOI: 10.1038/nrmicro.2017.173
|View full text |Cite
|
Sign up to set email alerts
|

Hopanoid lipids: from membranes to plant–bacteria interactions

Abstract: Lipid research represents a frontier for microbiology, as showcased by hopanoid lipids. Hopanoids, which resemble sterols and are found in the membranes of diverse bacteria, have left an extensive molecular fossil record. They were first discovered by petroleum geologists. Today, hopanoid-producing bacteria remain abundant in various ecosystems, such as the rhizosphere. Recently, great progress has been made in our understanding of hopanoid biosynthesis, facilitated in part by technical advances in lipid ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
137
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(146 citation statements)
references
References 141 publications
(116 reference statements)
4
137
0
5
Order By: Relevance
“…Biophysical studies, using artificial membranes, have demonstrated that hopanoids decrease the membrane permeability and increase the membrane order without compromising their mechanical properties (Sáenz et al, 2012, 2015; Mangiarotti et al, 2019a). In addition, and in accordance with in vitro studies, hopanoids promote resistance to antibiotics, detergents, extreme pHs, high temperature, oxidation, and high osmolarity in bacteria (Sáenz, 2010; Belin et al, 2018; Welander et al, 2010; Malott et al, 2014; Schmerk et al, 2011; Silipo et al, 2014; Kulkarni et al, 2013).…”
Section: Introductionsupporting
confidence: 70%
“…Biophysical studies, using artificial membranes, have demonstrated that hopanoids decrease the membrane permeability and increase the membrane order without compromising their mechanical properties (Sáenz et al, 2012, 2015; Mangiarotti et al, 2019a). In addition, and in accordance with in vitro studies, hopanoids promote resistance to antibiotics, detergents, extreme pHs, high temperature, oxidation, and high osmolarity in bacteria (Sáenz, 2010; Belin et al, 2018; Welander et al, 2010; Malott et al, 2014; Schmerk et al, 2011; Silipo et al, 2014; Kulkarni et al, 2013).…”
Section: Introductionsupporting
confidence: 70%
“…Through the MEP/DOXP pathway, geranyl–geranyl pyrophosphate and farnesyl pyrophosphate are produced and act as respective precursors for squalene and lycopene synthesis. Squalene is a triterpene precursor for the biosynthesis of bacterial hopanoids (Belin et al ., ), which are pentacyclic lipids involved in bacterial membrane fluidity and permeability (Rohmer et al ., ), with growing evidence suggesting roles in plant–bacteria rhizosphere interactions (Belin et al ., ). Lycopene is a precursor for carotenoids, a large family of photoreceptive C 40 polyene pigments produced by photosynthetic bacteria, algae, plants and fungi (Cuttriss et al ., ) which aid in photosynthesis and protection from photooxidation.…”
Section: Resultsmentioning
confidence: 99%
“…As Monk et al remark, the coverage of metabolic reactomes has stagnated, since little effort is spent on comprehensively uncovering the metabolic space of an organism, especially with regards to the secondary metabolism . A thorough analysis of these organisms may lead to interesting discoveries similar to, for instance, that of hopanoid production in M. capsulatus and Alicyclobacillus acidocaldarius …”
Section: Resultsmentioning
confidence: 99%